2011
DOI: 10.3846/bjrbe.2011.08
|View full text |Cite
|
Sign up to set email alerts
|

The Physically Nonlinear Analysis of Circular Plate on Deformable Foundation

Abstract: A circular reinforced concrete plate on deformable foundation is investigated. The foundation is composed of three layers of soil which are defined as isotropically nonlinear materials with variable physical properties. The reinforced plate is treated as an elastic body. The plate is subjected to dissymmetrical half-circular loading of linearly variable pressure. Generally, the unified system "structure-foundation" is the contact analysis problem, which is modeled by ANSYS software. Plastic shear deformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…for length (4 m) and amplitude loads (25, 75 and 100) kN, while the maximum vertical displacement occurs at time (0.5 sec.) for length (5 m) and the same amplitude loads, Figure (10). Also, it can be seen that the maximum vertical displacement takes place at time (0.47 sec.)…”
Section: Effect Of Foundation Lengthmentioning
confidence: 75%
“…for length (4 m) and amplitude loads (25, 75 and 100) kN, while the maximum vertical displacement occurs at time (0.5 sec.) for length (5 m) and the same amplitude loads, Figure (10). Also, it can be seen that the maximum vertical displacement takes place at time (0.47 sec.)…”
Section: Effect Of Foundation Lengthmentioning
confidence: 75%
“…These authors also reported analytical solutions for plates subjected to bending and free vibration. Additional studies on the behavior of foundation plates based on the Reissner-Mindlin theory can be found in [8], Wen and Aliabadi [9], and Jankovski and Skarzauskas [10]. In this last reference, the boundary element method was formulated in the Laplace domain to solve the problem.…”
Section: Introductionmentioning
confidence: 99%